Work ethics of different generational cohorts in South Africa - van der Walt, Freda; Jonck, Petronella; Sobayeni, Ntomzodwa Caroline (African Journal of Business Ethics, 2016)
Although generational differences have been studied in developed countries, not much information is available about generational cohorts and how they differ in terms of work ethics in developing countries. A cross-sectional study was conducted in 2014 with a sample of 301 respondents from South Africa. The work ethics of three generational cohorts, namely the Baby Boomers, Generation X and Generation Y, were measured. The main finding of this research was that statistically significant differences and similarities were found between the different generational cohorts in terms of certain facets of work ethics. Statistically significant generational differences were indicated for hard work and delay of gratification.
Published Article
Keywords: generational differences; work ethics; Generation Y; Generation X; Baby Boomers; hard work; delay of gratification; morality; ethics